2004
DOI: 10.1111/j.1365-2370.2004.00470.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of polymorphisms in the tumour necrosis factor alpha candidate gene in sheep

Abstract: Primers based on GenBank sequences of the ovine tumour necrosis factor (TNF)-alpha gene were designed to amplify a 273-bp fragment comprising part of the fourth exon and the 3' untranslated region (UTR) of the ovine TNF-alpha gene. Five different single-strand conformational polymorphism (SSCP) patterns were detected in a number of unrelated animals and three different alleles were identified and sequenced. These alleles differed in one deletion and one single nucleotide polymorphism (SNP) and were named TNF*0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
3
2
0
Order By: Relevance
“…Comparative analysis of the results obtained in our experiments revealed no indel variants in the goat TNF-a region, which agrees with the results of Alvarez-Busto et al (2004) in sheep. A study of immunodiversity in North American goat revealed that 272 bp of TNF-a were monomorphic (Shafer et al, 2012).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Comparative analysis of the results obtained in our experiments revealed no indel variants in the goat TNF-a region, which agrees with the results of Alvarez-Busto et al (2004) in sheep. A study of immunodiversity in North American goat revealed that 272 bp of TNF-a were monomorphic (Shafer et al, 2012).…”
Section: Discussionsupporting
confidence: 81%
“…This indicates the potential of strengthening variety improvement and promoting animal husbandry development in Chinese south domestic goats. In addition, similar results were observed for the class III TNF-a gene, and preliminary studies have identified variations in sheep (Alvarez-Busto et al, 2004); however, no difference was found in their frequencies between breeds. To date, the importance of these variations remains unclear.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The results of gel electrophoresis of PCR products revealed the presence of -238bp band, in addition to the -300,400 and 600bp desired fragment(Fig: ), from these results of PCR, we consider that, there was polymorphism in the TNF gene of aborted placental tissues ,and these results associated with fungal species isolates ,these results may be indicated that fungal infection of the placenta induced polymorphism of TNF-a genes ,these results were agreed with (23) who recommended that several immunogenetic polymorphisms in the human disease and HLA and cytokine gene are more relevant one ,also Roy et al, (24) explained that variation in the TNF alpha promoter region has been associated with severe forms of malaria ,Leishminiasis ,meningococcal infection and Leprosy. ,these findings were supported by observations of Alvarez et al (25) who identified three polymorphisms in TNFgene and also they recorded that the redesigned primers are shown below to amplify a TNF-alpha fragment that contains 90% of the original target sequence ,also other studies described two polymorphism in the human TNF alpha promoter at -308(19) and -238 (26).…”
Section: Molecular Examination Of Tnf Alpha Genesupporting
confidence: 74%